Identification of Airborne Aerobic Bacteria in the Intensive Care Room using MALDI-TOF MS - Palulun, Prajayanti; Rasita, Yoeke Dewi; Massi, Muhammad Nasrum; Sjahril, Rizalinda; Katu, Sudirman; Pattelongi, Ilhamjaya (Universitas Airlangga, 2024)
Introduction: Indoor air quality can affect the spread of airborne microorganisms which can lead to healthcare-associated infections (HAIs). The quality and quantity of airborne microorganisms are responsible for mortality and morbidity in infection-prone hosts such as patients admitted to the intensive care unit (ICU). The research aims to determine the quality of microorganisms in the air, identify the types of aerobic bacteria, and assess the physical parameters of the air in the ICU. Methods: This study was a cross-sectional study with a descriptive observational method. Air specimens were collected using the MAS-100 NT tool with blood agar plate solid culture media, which then incubated in an aerobic atmosphere for 24 hours at 37±2°C. Observation and measurement of air microbiological quality was by counting the number of microorganisms in CFU/m3 and identification of bacteria using MALDI-TOF MS. Results and Discussion: The maximum concentration of microorganisms in the air exceeds the standard value, and the average value of the concentration of microorganisms in the air is 736 CFU/m3. The most common types of aerobic bacteria in the air were Bacillus sp. (n=12), Coagulase-negative Staphylococci (n=5), and Staphylococcus aureus (n=5). There was an increase in physical parameters in the form of average temperature (26.24°C) and humidity (70%) with a ventilation system and air regulation using mechanical ventilation sourced from a split air conditioner with an exhaust fan without a high-efficiency particulate-absorbing (HEPA) filter. Conclusion: Low indoor air quality has the potential to increase the concentration of microorganisms and bacterial findings in the air